Calendar art activities in private schools Secondary School in Baghdad: سناء عبد الامير حسين (Al-Academy, 2016)
The technical activities designed to highlight the creations of students by providing activities appropriate to their abilities and capabilities within and outside the school, which is a way for the development of learning and learner behavior aimed at directing guidance educationally and artistically.As a result of the efforts of modern educational activities, art has become part of the philosophy of the modern school and part of the modern curriculum. Because it is enough to configure the practices and habits of a satisfactory and acceptable, and is characterized by precision, order and beauty.Through the researcher with a survey of previous studies that dealt with art activities and found that all studies have been confined to a calendar of these activities in public schools only, since the phenomenon of private schools a new phenomenon began in 2003 has increased in the recent increase is striking, prompting the researcher to study the reality of artistic activity in these schools is the civil and whether the required level and commensurate with the rapid developments taking place in Iraqi society at all levels, so the researcher felt that this is a problem it is necessary to pay attention to them. Therefore, considered to address identified ((calendar artistic activities in private schools at the secondary level in Baghdad))The current study targeted the following:1 - Studying the reality of artistic activities in the schools of civil secondary stage of the first breeding Rusafa in Baghdad.2 - Calendar artistic activities in the schools of civil secondary stage from the viewpoint of teachers and teachers of art education in it.The sample research (6) teacher and a school for art education at the secondary level out (30) teacher and a school were selected randomly, by (3) males and (3) of females, were selected (20%) of the total secondary school Of the (30) high school in the Directorate of Education / Rusafa one).The most important results that could be reached as follows: -1 - only the role of teachers and teachers of art education on the administration and supervision, and lacks the guidance and training students to artistic activities.2 - Number of students participating in artistic activities is the proportion of very weak compared with the total number of students in secondary schools.3 - did not adopt the high school civil claim of a complete artistic activities, these activities did not receive adequate support for their development